KAJIAN PERSEPSI MASYARAKAT TERHADAP PROGRAM PEMBERDAYAAN DI KAWASAN TAMAN NASIONAL BALURAN BERBASIS AHP (Analytical Hierarchy Process) - , Noviyani Utami, S.Hut; , Prof. Dr. Ir. H. Djoko Marsono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Baluran National Park is one of among the oldest national park in Indonesia, which the park surrounded by several villages. This condition has been resulted in high pressure to the park, such as wood and non wood harvesting from the park. The study aimed to